Thermo-orientation in fluids of arbitrarily shaped particles. Issue 1 (6th December 2018) - Gardin, Andrea; Ferrarini, Alberta
Abstract : The orientation of uncharged, chiral and achiral particles under a thermal gradient is explained in terms of geometric features of the particles. Abstract : Recent nonequilibrium Molecular Dynamics (NEMD) simulations revealed preferential orientation, induced by a temperature gradient, in fluids of uncharged dumbbell-like particles. The magnitude of this phenomenon, called thermo-orientation, was found to be linear in the applied temperature gradient and to increase with the difference in shape or mass between the two beads of the particles. The underlying mechanism and the microscopic determinants of the phenomenon are not obvious. Here, after examination of the general symmetry requirements for thermo-orientation, we have extended the NEMD simulations to uncharged particles of various shapes and mass distribution, including chiral cases. The numerical results are rationalized by a microscopic model, based on the assumption of local equilibrium. This allows us to correlate the thermo-orientation response of arbitrarily shaped particles to quantities that characterize their shape and mass distribution.